Effect of Late Planting Dates on Corn Yield - E. A. Adee; K. L. Roozeboom (Kansas Agricultural Experiment Station Research Reports, 2019)
Planting date studies have been conducted for corn over many years. Often the focus has been to determine the optimum planting date for maximizing yield. In some areas, planting early-maturing corn hybrids as early as possible has been a successful strategy for avoiding hot, dry conditions at the critical pollination and early grain fill stages. Planting later can be an alternative strategy that attempts to avoid the most intense heat by moving the critical growth stages for corn centered around pollination to later in the growing season. This strategy has been adopted by some growers in areas that often encounter heat and moisture stress during the growing season. However, crop insurance cutoff dates for planting are earlier than some farmers may want to plant their corn acres. The purpose of these studies was to assess the yield potential for corn planted after the insurance planting cutoff date and to compare corn yields from a wide range of planting dates.
Keywords: corn planting date; late planting corn